Up the Ladder of Concern: Youth and Young Adult Cannabis Use. - Isralowitz, Richard; Reznik, Alexander; Pruginin, Itay (International Journal of Mental Health & Addiction, 2018)
This paper aims to review patterns of cannabis (i.e., marijuana and hashish) use among high-risk Israeli youth and young adults based on research conducted by the Ben-Gurion University, Regional Alcohol and Drug Abuse Research Center. A total of 1074 Israeli youth (67.0% male, 33.0% female) were studied from 2004 to 2016. The youth and young adults included those placed in residential programs for learning and/or behavior problems (youth villages) and were school dropouts referred to a 90-day treatment facility for drug abuse. Country of origin, determined by mother’s birthplace, revealed 42.4% of the youth was of Israeli origin and 57.6% from other countries—mostly the former Soviet Union and Ethiopia. About “village” youth, no gender or religious status (secular/non-secular) differences were found for lifetime and last month cannabis use. Immigrant origin youth, than those with Israeli status, reported more lifetime and last month use as well as cannabis availability. Youth from families with low socio-economics status reported a higher rate of last month cannabis use than those with better economic conditions. Among school dropouts, no gender or religious status differences were found for lifetime and last month cannabis use and availability. For all study youth, binary logistic regression results indicated six factors significantly predicted last month cannabis use: male gender, age, last month binge drinking, illicit drug selling, reduced relations with friends, and cannabis availability. In terms of policy and service provision, high-risk youth (e.g., those in residential programs, whether for learning and/or behavior problems) should be priority for drug prevention efforts.